Factors Affecting Adherence to Iron-Folic Acid Supplementation During Pregnancy in Rawalpindi - Mughal, Fatima Ali Raza; Azam, Naila; Asif, Raima; Khan, Najam us Saqib; Riaz, Mehwish (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To determine frequency of adherence to Iron Folic Acid supplementation (IFAS) and to identify determinants of adherence to IFAS in pregnant women of Rawalpindi. Study Design: Cross-sectional study. Place and Duration of Study: Department of Gynecology and Obstetrics, Fauji Foundation Hospital, Rawalpindi, Pakistan, from Oct 2021 to Mar 2022. Methodology: Three hundred and ninety-nine pregnant women in their second and third trimesters of pregnancy meeting our inclusion criteria were recruited. A pre-validated, open-access questionnaire, including informed consent, demographic information, and items related to IFAS adherence, including reasons for non-adherence, counselling by healthcare provider, polypharmacy, family support, and whether or not the pregnancy was planned, was administered. Results: Forgetfulness (23.7%), abdominal pain (13.4%), nausea (14.4%), and unpleasant taste (11.3%) were main reasons reported for non-adherence. There was a significant association between education (p=0.001), monthly income (p=0.03), area of residence (p=0.001), planned pregnancy (p=0.001), husband’s support (p< 0.001), counseling by healthcare provider regarding the importance of IFAS (p=0.003), availability (p< 0.001), accessibility (p< 0.001) and affordability (p< 0.001) of IFAS supplements and adherence. Conclusion: The majority of women reported adherence to the prescribed IFAS supplementation. Higher education, planned pregnancy, urban residence, husband’s support, counselling by healthcare provider, affordability, availability and accessibility were associated with adherence. For those who reported non-adherence, forgetfulness and side effects were main reasons reported for non-adherence. Training of healthcare professionals to provide better counseling to women and their husbands during Antenatal care is recommended.